Large Lytic Defects Produce Kinematic Instability and Loss of Compressive Strength in Human Spines: An in Vitro Study. (19th May 2021) - Alkalay, Ron N.; Adamson, Robert; Miropolsky, Alexander; Davis, Roger B.; Groff, Mike L.; Hackney, David B.
Abstract : Background: In patients with spinal metastases, kinematic instability is postulated to be a predictor of pathologic vertebral fractures. However, the relationship between this kinematic instability and the loss of spinal strength remains unknown. Methods: Twenty-four 3-level thoracic and lumbar segments from 8 cadaver spines from female donors aged 47 to 69 years were kinematically assessed in axial compression (180 N) and axial compression with a flexion or extension moment (7.5 Nm). Two patterns of lytic defects were mechanically simulated: (1) a vertebral body defect, corresponding to Taneichi model C (n = 13); and (2) the model-C defect plus destruction of the ipsilateral pedicle and facet joint, corresponding to Taneichi model E (n = 11). The kinematic response was retested, and compression strength was measured. Two-way repeated-measures analysis of variance was used to test the effect of each model on the kinematic response of the segment. Multivariable linear regression was used to test the association between the kinematic parameters and compressive strength of the segment. Results: Under a flexion moment, and for both models C and E, the lesioned spines exhibited greater flexion range of motion (ROM) and axial translation than the control spines. Both models C and E caused lower extension ROM and greater axial, sagittal, and transverse translation under an extension moment compared with the control spines. Two-way repeated-measures analysis revealed that model E, compared with model C, caused significantly greater changes in extension and torsional ROM under an extension moment, and greater sagittal translation under a flexion moment. For both models C and E, greater differences in flexion ROM and sagittal translation under a flexion moment, and greater differences in extension ROM and in axial and transverse translation under an extension moment, were associated with lower compressive strength of the lesioned spines. Conclusions: Critical spinal lytic defects result in kinematic abnormalities and lower the compressive strength of the spine. Clinical Relevance: This experimental study demonstrates that lytic foci degrade the kinematic stability and compressive strength of the spine. Understanding the mechanisms for this degradation will help to guide treatment decisions that address inferred instability and fracture risk in patients with metastatic spinal disease.